2007
DOI: 10.1074/jbc.c700061200
|View full text |Cite
|
Sign up to set email alerts
|

Fukutin-related Protein Associates with the Sarcolemmal Dystrophin-Glycoprotein Complex

Abstract: Mutations in fukutin-related protein (FKRP) give rise to mild and more severe forms of muscular dystrophy. FKRP patients have reduced glycosylation of the extracellular protein dystroglycan, and FKRP itself shows sequence similarity to glycosyltransferases, implicating FKRP in the processing of dystroglycan. However, FKRP localization is controversial, and no FKRP complexes are known, so any FKRP-dystroglycan link remains elusive. Here, we demonstrate a novel FKRP localization in vivo; in mouse, both endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
2
28
2
Order By: Relevance
“…3E). This is in contrast to other muscular dystrophies involving the DGC, where one primary genetic defect leads to disruption of the entire DGC, as assessed by using the same assay (27,28). This finding indicates that it is not the loss of the entire DGC, but rather the disrupted linkage between the sarcolemma and the basal lamina (due to disrupted glycosylation of ␣-DG) (Fig.…”
Section: Large Myd Muscle Maintains An Intact Dgc But Is Highly Suscementioning
confidence: 39%
“…3E). This is in contrast to other muscular dystrophies involving the DGC, where one primary genetic defect leads to disruption of the entire DGC, as assessed by using the same assay (27,28). This finding indicates that it is not the loss of the entire DGC, but rather the disrupted linkage between the sarcolemma and the basal lamina (due to disrupted glycosylation of ␣-DG) (Fig.…”
Section: Large Myd Muscle Maintains An Intact Dgc But Is Highly Suscementioning
confidence: 39%
“…For secondary immunofluorescence, tissues were blocked with 5% donkey serum in PBS, incubated in primary antibody overnight, washed, incubated in Cy3 (Jackson ImmunoResearch Laboratories Inc.) or Alexa Fluor 488-conjugated (Molecular Probes, Invitrogen) secondary antibodies, washed, and coverslipped. With the exception of αDG glycosylation staining, tissue cryosections were processed for immunofluorescence as described previously (81). For αDG glyco-antibody IIH6, tissues were fixed in 2% PFA, washed, and denatured by incubations with 100 mM glycine at room temperature and 0.05% SDS at 50°C for 10 and 30 minutes, respectively (82).…”
Section: Methodsmentioning
confidence: 99%
“…PHOS-bead voids were buffer exchanged (same as desalting step) and concentrated, diluted 1:1 with phosphate buffer, and mixed with 5×LSB for SDS-PAGE. All protein samples were separated by 3%-15% SDS-PAGE and transferred to PVDF for Western blotting using standard protocols (81). Laminin overlays have been described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…According to yamamoto et al 25 , although the functions of fukutin continue unclear, it seems to interact with alpha-DG during glycosylation but binding to the core area of alpha-DG instead of its sugar chain. Also concerning FKrP, it has recently been supposed that in normal and mutant mice it is detected in the sarcollema and coexists with DG in the native dystrophin-glycoprotein complex, perhaps having its localization mediated by DG 26 . It has not yet been demonstrated that lArGe is a glycosyltransferase itself but the Kanagawa et al 27 found that alpha-DG interacts with lArGe at two different domains, one involved with the glycosilation process itself and the other at intracellular level (N-terminal domain of α-DG) for defining a recognition motif necessary to initiate functional glycosylation.…”
Section: Fig 1 Schematic Representation Of the Main Proteins Involvementioning
confidence: 99%